Photon-Counting Computed Tomography (PC-CT) of the spine: impact on diagnostic confidence and radiation dose - Rau, Alexander; Strähle, Jakob; Stein, Thomas; Diallo, Thierno; Rau, Stephan Georg; Faby, Sebastian; Nikolaou, Konstantin; Schönberg, Stefan; Overhoff, Daniel; Beck, Jürgen; Urbach, Horst; Klingler, Jan-Helge; et al. (European radiology, 2023)
Computed tomography (CT) is employed to evaluate surgical outcome after spinal interventions. Here, we investigate the potential of multispectral photon-counting computed tomography (PC-CT) on image quality, diagnostic confidence, and radiation dose compared to an energy-integrating CT (EID-CT).
Online veröffentlicht: 9. März 2023
Gesehen am 04.04.2024